Evaluation of Frequency and Type of Severe Anemia in Patients Referred to the Baqiyatallah Hospital in Tehran in Six Months; A Descriptive Cross-Sectional Study - Jalalian, Hamid Reza; Shasti, Meysam; Mahmoudi, Sadrollah; Goodarzi, Hassan (International Journal of Statistics in Medical Research, 2022)
Purpose: To investigate the frequency and types of severe unknown anemia in patients referred to the Baqiyatallah Hospital (Tehran) for six months. Methods: In this descriptive cross-sectional study, the patients with severe unknown anemia referred to the Baqiyatallah Hospital (Tehran, Iran) were selected over six months. Following consideration of inclusion and exclusion criteria, 230 patients with severe anemia (hemoglobin (Hb) > 8gr/dl) were included. Complete medical history was obtained from the patients and additional biochemical blood analyses were applied to determine the frequency and type of anemia. SPSS (v.19) software was used to analyze the findings and the significance level was defined as a p-value <0.05. Results: In chronic disease anemia (47.5%), gastrointestinal bleeding-associated anemia (29%), bleeding malignancies anemia (21.5%), and aplastic anemia (2%). There were significant differences (p<0.05) in the frequency of different types of normocytic anemia. The highest frequency was detected in folate deficiency anemia (46%), hypothyroidism anemia (34%), and B12 deficiency anemia (20%), respectively. The hemolytic anemia represented a significant difference (p<0.05) in comparison with sickle cell anemia (95%). Also, sickle cell anemia showed a significant difference (p<0.05) between thalacemia-associated anemia (95%) and malignancy-related anemia (95%) Conclusion: Respectively, the highest frequency of anemia in patients was found in chronic diseases and gastrointestinal bleeding. It is suggested that more attention should be paid to the type of anemia of patients referred to the urgency of hospitals.